PCR Detection and Serological Evidence of Granulocytic Ehrlichial Infection in Roe Deer (Capreolus capreolus) and Chamois (Rupicapra rupicapra) - Liz, Jorge S.; Sumner, John W.; Pfister, Kurt; Brossard, Michel (My University, 2002)
The role of wild mammals, such as roe deer (Capreolus capreolus) and chamois (Rupicapra rupicapra), in the epidemiology of granulocytic ehrlichiae in Switzerland was investigated. We tested blood samples for Ehrlichia phagocytophila genogroup 16S rRNA gene sequences by PCR and for immunoglobulin G antibodies against granulocytic ehrlichiae by indirect fluorescent-antibody assay (IFA). Overall means of 60.9% of 133 roe deer serum samples and 28.2% of 39 chamois serum samples were seroreactive by IFA. PCR results were positive for 18.4% of 103 roe deer serum samples as well. None of the 24 chamois blood samples tested were positive by PCR. Partial 16S rRNA gene and groESL heat shock operon sequences of three roe deer samples tested showed strong degrees of homology (99.7 and 98.6%, respectively) with the sequences of granulocytic ehrlichiae isolated from humans. These results confirm that chamois, and particularly roe deer, are commonly infected with granulocytic ehrlichiae and provide evidence that these wild mammals are potential reservoirs for granulocytic ehrlichiae in Switzerland.